Emotion Regulation Difficulties During and After Partial Hospitalization Treatment Across Eating Disorders. Issue 3 (May 2020) - Brown, Tiffany A.; Cusack, Anne; Berner, Laura A.; Anderson, Leslie K.; Nakamura, Tiffany; Gomez, Lauren; Trim, Julie; Chen, Joanna Y.; Kaye, Walter H.
Abstract: Emotion regulation deficits are associated with eating disorder (ED) symptoms, regardless of eating disorder diagnosis. Thus, recent treatment approaches for EDs, such as dialectical behavior therapy (DBT), have focused on teaching patients skills to better regulate emotions. The present study examined changes in emotion regulation among adult patients with EDs during DBT-oriented partial hospital treatment, and at follow-up (M[SD] = 309.58[144.59] days from discharge). Exploratory analyses examined associations between changes in emotion regulation and ED symptoms. Patients with anorexia nervosa, restricting (AN-R, n = 77), and binge-eating/purging subtype (AN-BP, n = 46), or bulimia nervosa (BN, n = 118) completed the Difficulties in Emotion Regulation Scale (DERS) at admission, discharge, and follow-up. Patients with BN demonstrated significant improvements across all facets of emotion dysregulation from admission to discharge and maintained improvements at follow-up. Although patients with AN-BP demonstrated statistically significant improvements on overall emotion regulation, impulsivity, and acceptance, awareness, and clarity of emotions, from admission to discharge, these improvements were not significant at follow-up. Patients with AN-R demonstrated statistically significant improvements on overall emotion dysregulation from treatment admission to discharge. Changes in emotion regulation were moderately correlated with changes in ED symptoms over time. Results support different trajectories of emotion regulation symptom change in DBT-oriented partial hospital treatment across ED diagnoses, with patients with BN demonstrating the most consistent significant improvements. Highlights: Emotion dysregulation plays an important role in eating disorder psychopathology Patients with bulimia nervosa improved on emotion regulation through follow-up Anorexia, binge-purge patients did not maintain improvements through follow-up Anorexia, restricting patients had fewer emotion regulation improvements over time